The Impact of Agricultural Waste and Residue Composts on Two Consecutive Spinach Cultivations: 1- Response of Soil Fertility Indicators, Plant Nutrient Uptake, and Yield - Kh. Salarinik; M. Nael (مجله آب و خاک, 2024)
IntroductionLarge amounts of agricultural waste such as straw, leaves and pulps, with high nutritional value are produced every year. Grape pomace (GP) is rich in macro- and micro-nutrients and can be used as a soil amendment. However, due to its slow decomposition rate and the spread of diseases and pests, it should not be applied directly to the soil. Therefore, GP is composted in combination with other wastes. There is not enough information about the composting of GP and the effect of the produced composts on soil fertility in Iran. Hence, the aims of this study were twofold: to explore the impact of various GP composts on both soil fertility and spinach yield, relative to two levels of urea fertilizer, through a pot experiment conducted over two consecutive cultivation seasons; to categorize soil treatments based on fertilization regimes and timing (season), thus elucidating any patterns or trends in the observed effects. Materials and MethodsTo investigate the effects of GP composts on soil fertility and spinach (Persius hybrid) yield, was conducted as a randomized complete block design with eight compost treatments, two levels of urea fertilizer (46%), and a control treatment (C0), in three replications and two continuous cropping seasons (spring and fall). Compost treatments included: high grape pomace (HG) (60-63%) with chickpea straw and alfalfa (HG-Ch-A), high GP with chickpea straw and sugar beet pulp (HG-Ch-B), high GP with alfalfa and sugar beet pulp (HG-A-B), high GP combined with chickpea straw, alfalfa, and sugar beet pulp (HG-All); four other compost treatments included low level of grape pomace (LG) (37-42%) combined with other residues/wastes similar to the first four treatments (LG-Ch-A, LG-Ch-B, LG-A-B, and LG-All). Urea treatments included: 150 kg per hectare (C150) (two-step top dressing) and 500 kg per hectare (C500) (three-step top dressing). A sandy loam soil was used for this experiment. The composts were separately mixed into the soil at a rate of 2% (by weight(. The first crop was grown for 50 days in May 2018 and the second crop was grown for 45 days in September 2018. In both seasons, the fresh and oven-dried weigh of spinach shoot and root were determined. Also, total concentration of K, Na, Ca, Mg, P, Fe, Zn, Cu, and NO3- were measured in spinach to determine the amount of soil elements taken up by the crop. In both seasons, soil pH and EC, and contents of soil organic carbon (OC), active carbon (AC), total nitrogen (TN), NO3-, NH4+, and exchangeable K, Ca, Mg, and Na, as well as available forms of P, Fe, Cu, and Zn were determined. One-way ANOVAs were applied separately to spring and fall data, and mean comparisons were made using Duncan's test at 0.05% level. To determine the similarities and dissimilarities of the different treatments based on their effect on soil characteristics, cluster analysis was performed on all soil characteristics that showed significant differences between treatments. Results and DiscussionIn both cultivation periods, TN levels exhibited no significant variance across treatments. Notably, the highest potassium (K) levels were consistently observed in the HG-All and LG-All treatments, while the lowest K levels were consistently recorded in the C0, C150, and C500 treatments. In the initial cultivation period, no notable differences were observed between the C0, C150, and C500 treatments, except for potassium (K) and ammonium (NH4+), with significantly higher levels detected in the C0 treatment. Conversely, during the second cultivation period, significant disparities were observed among the C0, C150, and C500 treatments solely in terms of nitrate (NO3-) content, with notably higher nitrate levels detected in the C150 and C500 treatments. Through cluster analysis, all treatments from both cultivation periods were categorized into five distinct groups. Specifically, the C0, C150, and C500 treatments for each season were consistently grouped together, respectively, into groups one and two. All compost treatments of each season, except the HG-All treatment in the spring cultivation, were grouped into one class. In the second cultivation, the HG-Ch-A showed significantly higher EC than all treatments, except the HG-Ch-B. The LG-A-B treatment showed the highest amount of OC and C/N (in both cultivations), and NH4+ and Cu (in the second cultivation). The HG-Ch-A and HG-Ch-B treatments increased TN, P, K, Mg, OC, and AC in the second cultivation compared to the first. The amounts of all macronutrients and micronutrients, except Fe and Ca, increased in the compost treatments compared to the control and chemical treatments. In addition, an increase in EC was observed in the compost treatments compared to the control and chemical treatments, and an increase in pH compared to the C500 treatment. In the first cultivation, the LG-Ch-A and C500 treatments had significantly higher yields than the control. In the second cultivation, the LG-All, HG-All, HG-Ch-A, and LG-A-B treatments were the best compost treatments, while the LG-Ch-B and HG-Ch-B treatments were the weakest treatments in terms of soil fertility and plant yield. In both seasons, the absorption of elements by spinach depended on multiple factors, including the element type, its available content in the soil, its initial content in the composts (or fertilizer), soil pH, and yield. ConclusionThe application of GP composts over two consecutive growing seasons increased the levels of nitrogen, phosphorus, potassium, magnesium, zinc, copper, active carbon and organic carbon in the soils. These results are very important as magnesium, copper and zinc are rarely applied by farmers. In contrast, depletion of all elements, except organic carbon, occurred in the control and chemical fertilizer treatments due to plant uptake of elements. The combination of chickpea straw with sugar beet pulp is not recommended for the production of GP compost, especially at low GP levels, due to its minimal effect on soil fertility and plant yield. Despite the positive effect of the GP composts in increasing soil fertility, the continuous application of large amounts of these composts is not recommended in the arid regions due to the increase in soil EC and pH. The difference between the compost treatments after two applications of GP composts was less than after one application; these results were confirmed by cluster analysis, in the sense that all compost treatments in the second season were placed in one cluster.